2022
DOI: 10.1097/wnp.0000000000000924
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Neurophysiological Monitoring Alerts During Three-Column Osteotomy: Incidence and Risk Factors

Abstract: Prupose: To analyze the incidence and risk factors of intraoperative neurophysiological monitoring (IONM) alerts in patients undergoing three-column osteotomy.Methods: A total of 551 patients (340 males and 211 females) with an average age of 31.9 years undergoing posterior 3-column osteotomy were retrospectively reviewed. The coronal Cobb angle of main curve and sagittal global kyphosis were measured on preoperative standing whole spinal x-rays. The Frankel scores at preoperation, postoperation, and the last … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Any irritation to the spinal cord during procedures such as apical pediculectomy, circumferential spinal cord decompression, and osteotomy might lead to temporary decreases in IONM waveforms, particularly in MEP monitoring. Another study 11 involving 551 patients undergoing 3CO reported 17.8% IONM alerts during surgery, aligning more closely with our findings due to similar criteria for defining such alerts.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Any irritation to the spinal cord during procedures such as apical pediculectomy, circumferential spinal cord decompression, and osteotomy might lead to temporary decreases in IONM waveforms, particularly in MEP monitoring. Another study 11 involving 551 patients undergoing 3CO reported 17.8% IONM alerts during surgery, aligning more closely with our findings due to similar criteria for defining such alerts.…”
Section: Discussionsupporting
confidence: 90%
“…IONM alerts were triggered when (1) an increase in somatosensory-evoked potentials (SSEP) latency exceeding 10%; (2) a decrease in SSEP amplitude exceeding 50%; and (3) a decrease in motor-evoked potentials (MEP) amplitude exceeding 80% 10,11 . It is imperative to initially exclude interference from anesthesia and monitoring workstations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation